(untitled) (Herald of Journalism, 2020)
The article was a comparison and analysis of the situation with the kazakh aphorisms and aphorisms akyn Kadir Ali Mirza’s. Has been studied extensively and the evaluation of the structure, ideological and artistic sin- gularity aphorisms bard.